Knowledge and insights from a maturing international clinical quality registry. (20th January 2022) - Sampurno, Fanny; Kowalski, Christoph; Connor, Sarah E; Nguyen, Anissa V; Acuña, Àngels Pont; Ng, Chi-Fai; Foster, Claire; Feick, Günter; Boronat, Olatz Garin; Dieng, Sebastian; Brglevska, Silvana; Ferrante, Stephanie; et al.
Abstract: Since 2017, the TrueNTH Global Registry (TNGR) has aimed to drive improvement in patient outcomes for individuals with localized prostate cancer by collating data from healthcare institutions across 13 countries. As TNGR matures, a systematic evaluation of existing processes and documents is necessary to evaluate whether the registry is operating as intended. The main supporting documents: protocol and data dictionary, were comprehensively reviewed in a series of meetings over a 10-month period by an international working group. In parallel, individual consultations with local institutions regarding a benchmarking quality-of-care report were conducted. Four consensus areas for improvement emerged: updating operational definitions, appraisal of the recruitment process, refinement of data elements, and improvement of data quality and reporting. Recommendations presented were drawn from our collective experience and accumulated knowledge in operating an international registry. These can be readily generalized to other health-related reporting programs beyond clinical registries.